Deteksi Cemaran Bakteri Salmonella spp. pada Ikan Bandeng Segar (Chanos chanos) di Tempat Pelelangan Ikan Gadukan Lumpur Kabupaten Gresik - Putra, Liantika Versa Dharma (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Salmonella spp. is a bacterium that causes Salmonellosis and is a bacterium that can cause food-borne illness to humans. The presence of Salmonella spp. in fresh milkfish can affect quality aspects, quality deterioration in fishery products, and food safety. Microbiological testing is an important indicator in checking for contamination in food. The main factor causing contamination can be the presence of pathogenic bacterial contamination in food ingredients. The purpose of this study was to detect Salmonella spp. on fresh milkfish (Chanos chanos) sold at Fish Auction Places (FAP), Gresik Regency using the Total Plate Count (TPC) test indicator and Salmonella Shigella Agar (SSA) media culture. This study used a qualitative descriptive study which began with observing the location and taking samples of milkfish in the field, then proceeding with the isolation of Salmonella spp. from in-vitro samples of milkfish and analyzed qualitatively. The results showed that fresh milkfish samples were contaminated with microbes with the highest number of 6Ã—105 CFU/g and were detected to contain Salmonella spp. on SSA media, so that milkfish sold at the Gadukan Lumpur Fish Auction Place in Gresik Regency cannot meet the Indonesian National Standard for fresh fish (2729-2021).